Pengaruh keputusan wasit yang ada dalam pertandingan sepakbola - Lazuardhi, Alex Febryan (Maliki Interdisciplinary Journal, 2024)
Football is a very popular sport and involves participation from all ages. The referee's decision is an important element that influences the progress of the match and also the final result of the match. Factors such as the referee's age, experience, physical health and emotional condition greatly influence his decisions. In addition, pressure from the crowd, team protests and media expectations greatly influence the quality of decisions taken. VAR (Video Assistant Referee) technology was introduced as a solution to reduce referee errors in making important decisions, although implementation has not been widespread in developing countries due to cost constraints. Recommendations to improve the quality of refereeing decisions include intensive training for technical and mental skills, wider implementation of VAR, management of external pressure, as well as monitoring excessive player protests.